Prescriptions written by MBBS Interns in the Department of Psychiatry in a Medical College Hospital in Mangaluru: A Quality Improvement Study [version 2; peer review: 3 approved] - Poorva Bakshi; Sharanya B. Shetty; Keshava Pai; Shreya Bera; Priyanka Renita D'Souza (F1000Research)
Background Rational prescription writing is an important skill to master during internship. This Quality Improvement (QI) project aimed to understand the state of prescription writing among interns posted in the Department of Psychiatry, analyze the causes responsible for errors in prescription writing and bring about a change in the current practice. Methods The MBBS interns are posted in the Department of Psychiatry for 15 days. During day 1 to day 5 of their posting, a pre intervention phase was conducted wherein prescriptions written by interns in the Department of Psychiatry were collected. The prescriptions were scored based on 14 criteria which were selected based on World Health Organization (WHO) guidelines and Medical Council of India (MCI) ideal prescription format. During PDSA (Plan Do Study Act) Cycle 1, an educational handout was distributed to the interns containing the MCI ideal prescription format and WHO guidelines regarding prescription writing. The brochure was also verbally explained to the interns. From day 7 to day 15 of their posting, prescriptions written by the interns were collected. The prescriptions were scored using the same criteria. Results During the pre intervention phase the mean total score of prescriptions was 9.54 ± 1.003. There was a significant improvement in the mean total score to 10.26 ± 0.746. There was a 7.54% improvement. There was also a significant improvement in several individual criteria. Conclusions The first PDSA cycle was successful in improving the quality of prescription writing among interns posted in the Department of Psychiatry. There is a need to implement more PDSA cycles to improve the quality still further.